Momentos-chave na experiência do omnishopper: um estudo construtivista da teoria fundamentada em dados - Pastore, Ricardo (2020)
Retail has become an activity that mixes physical and digital touchpoints. Retail companies are struggling to integrate them under omnichannel strategies, in order to meet users' requirements that, on the other hand, develop quickly new pieces of knowledge applied immediately to their shopping experiences, seeking to exceed their expectations regarding utility and pleasure. It shows a concept model proving that users enjoy researching and, thus, it develops new cognitive resources that are applied in shopping experiences triggering new emotional resources development. The new cognitive and emotional resources are applied to the touchpoints to carry out experiences evaluated in the end by the meaning to the users' life. A constructivist study of Grounded Theory (Charmaz, 2014) was carried out to theorize key moments in users' experience at retail touchpoints. Data was the collection in two phases were performed, the first for convenience, with a sample of five participants and the other theoretical, with eleven. The data were collected through the WhatsApp audio application, transcribed using the Google Documents Dictate feature. The codes were constructed using Quirkos. The key moments are stated as contact made with the use of cognitive and emotional resources and evaluated as those that make sense in users' experiences in omnichannel retail